Ethics and animal experimentation: what is debated? - Rita Leal Paixão; Fermin Roland Schramm
The purpose of this article is to raise some points for an understanding of the contemporary debate over the ethics of using animals in scientific experiments. We present the various positions from scientific and moral perspectives establishing different ways of viewing animals, as well as several concepts like 'animal ethics', 'animal rights', and 'animal welfare'. The paper thus aims to analyze the importance and growth of this debate, while proposing to expand the academic approach to this theme in the field of health.